1995
DOI: 10.1002/recl.19951140202
|View full text |Cite
|
Sign up to set email alerts
|

Role of the stereochemistry of 3′‐fluoro‐3′‐deoxy analogues of 2‐5A in binding to and activation of mouse RNase L

Abstract: Abstract. The synthesis of two sets of analogues of 2-5A trimer containing 943-fluoro-3-deoxy-P-D-xylo-furanosy1)adenine (AF) or 3'-fluoro-3'-deoxyadenosine (A F) at different positions of the chain is described, along with the preparation of the corresponding 5'-monophosphates and 5'-diphosphorylated (core) trimers. The ability of each rib0 and xylo isomeric pair of fluorodeoxy analogues of 2-5A ( i ) to compete with p3(A2'p),A3'[32P]pC3'p for binding to RNase L in L929 cell extracts, and (ii) to activate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The study of the ability of 2-5A fluorodeoxyanalogs to bind and activate RNase L showed that the analog whose fluorine atom in the xylo-configuration in the midmoiety is nine times more active than the parent mediator, 2-5A and about 280 times more effective than isomeric ribo-trimer [32][33][34]. The results suggest that anti↔syn stereochemical differences between pppAA(A F ) and pppAA(A F ), on the one hand, and related 8-bromo-and -methyl-analogs, on the other hand, cause differences in the degree of RNase L activation.…”
Section: The Role Of Structural and Stereochemical Factors In Binding...mentioning
confidence: 99%
See 1 more Smart Citation
“…The study of the ability of 2-5A fluorodeoxyanalogs to bind and activate RNase L showed that the analog whose fluorine atom in the xylo-configuration in the midmoiety is nine times more active than the parent mediator, 2-5A and about 280 times more effective than isomeric ribo-trimer [32][33][34]. The results suggest that anti↔syn stereochemical differences between pppAA(A F ) and pppAA(A F ), on the one hand, and related 8-bromo-and -methyl-analogs, on the other hand, cause differences in the degree of RNase L activation.…”
Section: The Role Of Structural and Stereochemical Factors In Binding...mentioning
confidence: 99%
“…The results suggest that anti↔syn stereochemical differences between pppAA(A F ) and pppAA(A F ), on the one hand, and related 8-bromo-and -methyl-analogs, on the other hand, cause differences in the degree of RNase L activation. Data presented in [32][33][34] suggest the syn-orientation is a major contribution to this process. The pppA(A F )A F poor ability to activate RNase L supports this assumption.…”
Section: The Role Of Structural and Stereochemical Factors In Binding...mentioning
confidence: 99%